Innovating higher education teaching in economics: cooperative learning and participative elaboration of contents - Gonzalo Caballero Miguez; María Dolores Garza Gil (Universitat Politècnica de València, 2012)
This paper presents an innovating experience in the teaching of Applied Economics based on cooperative learning and the participative elaboration of contents, carried out in the teaching of International Economic Structure and Economics of Public Sector in the Department of Applied Economics at the University of Vigo. The educational system combines skillful teaching with a set of practices and directed activities - including the accomplishment of cooperative learning- in which the competences of the students are developed. The cooperative learning carried out in groups of students is incorporated into the general contents of the course, being evaluated. This activity implies that students develop an active role in the configuration of the course, and students exercise their competences through cooperative learning and the participative elaboration of contents. This form of content elaboration is the main educative innovation of this case-analysis.